The impact of campus buses on disease spreading via contact networks - Hay, Nicolette Shu Ying (Nanyang Technological University, 2023)
Although the world is progressively emerging from the COVID-19 pandemic, the spread of infectious diseases remains a major threat to public health. As people return to normalcy, these human movements, especially via the means of public transportation, is a contributing factor to the persistence of the novel coronavirus to date. It is also important to identify potential hotbeds for diseases to spread, and one such place is school campuses where young students spend long durations at. Thus, it is necessary to analyze human encounters and identify transmission chains to control disease spread. This project studies the influence of a transportation system of a university campus on disease spread via contact networks. Synthetic data are created to represent passenger traffic in the transportation system, and contact networks are formed. Through analyses of contact networks, ways to control or minimize disease spread are identified.